GIVING TEMULAWAK AND KUNYIT EXTRACT TO INCREASE PRODUCTIVITY AND AS AN AVIAN INFLUENZA IMMUNOSTIMULATOR ON BROILER CHICKEN - Sutarto, Sutarto (Universitas Djuanda Bogor, 2019)
Broiler chickens in Indonesia have good prospects to develop. However, there are many obstacles that must be faced by broiler breeders, such as soaring prices of feed and medicine, harvest prices that tend to fluctuate, and the outbreak of bird flu that has not yet been found. The objective of the experiment was to investigate the effectiveness of treating broiler with temulawak and kunyit extracts to enhance productivity and as imunostimulator of avian influenza. Broiler were given either temulawak, kunyit or temulawak+kunyit extracts. The treatments, including a control, were arranged in a factorial design. Variables measured were production index and immune titter with haemaglutination Inhibition (HI) test at 35 days of age.Results showet that control, temulawak, kunyit and temulawak+ kunyit treated chicken have production indexes of 302,10; 387,11; 324,52; and 354,70, respectively. Haemaglutination Inhibition (HI) test result were all negative. It can be concluded that neither temulawak, kunyit or temulawak+ kunyit extracts is effective immunostimulator of avian influenza in broiler. Nevertheless, temulawak-treated chicken showed highest production index.Key Words : Temulawak, Kunyit, Avian Influenza, Haemaglutination Inhibition